Mantle Cell Lymphoma of Mucosa-Associated Lymphoid Tissue: A European Mantle Cell Lymphoma Network Study. Issue 1 (February 2020) - Morello, Lucia; Rattotti, Sara; Giordano, Laura; Jerkeman, Mats; van Meerten, Tom; Krawczyk, Katarzyna; Moita, Filipa; Marino, Dario; Ferrero, Simone; Szymczyk, Michał; Aurer, Igor; El-Galaly, Tarec Christoffer; et al.
Abstract : Abstract: While classical nodal mantle cell lymphoma (cMCL) is often associated with involvement of multiple extranodal sites, isolated extranodal disease (ED) at the time of diagnosis is a rare event; data on the outcome of these forms are lacking. On behalf of the European MCL Network, we conducted a retrospective analysis on the clinical characteristics and outcomes of MCL presenting with isolated or predominant ED (MALT MCL). We collected data on 127 patients with MALT MCL diagnosed from 1998 to 2015: 78 patients (61%) were male with a median age of 65 years. The involved sites include: upper airways + Waldeyer ring (40; 32%), gastrointestinal tract (32; 25%), ocular adnexa (17; 13%), oral cavity and salivary glands (17; 13%) and others (13; 1%); 7 patients showed multiple extranodal sites. The median follow-up was 80 months (range: 6–182), 5-year progression-free survival (PFS) was 45% (95% CI: 35–54) and 5-year overall survival (OS) was 71% (95% CI: 62–79). In an explorative setting, we compared MALT MCL with a group of 128 cMCL patients: MALT MCL patients showed a significantly longer PFS and OS compared with nodal cMCL; with a median PFS of 4.5 years vs 2.8 years (p = 0.001) and median OS of 9.8 years vs 6.9 years (p = 0.018), respectively. Patients with MALT MCL at diagnosis showed a more favorable prognosis and indolent course than classical nodal type. This clinical variant of MCL should be acknowledged to avoid possible over-treatment. Abstract : Supplemental Digital Content is available in the text